2021
DOI: 10.21203/rs.3.rs-209540/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Performance in Three-hands Tasks

Abstract: The successful completion of complex tasks like hanging a picture or laparoscopic surgery requires coordinated motion of morethan two limbs. User-controlled supernumerary robotic limbs (SL) have been proposed to bypass the need for coordination witha partner in such tasks. However, neither the capability to control multiple limbs alone relative to collaborative control with partners, nor how that capability varies across different tasks, is well understood. In this work, we present an investigation of tasks re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Compared to the results of [15], which considered the same coupled motion task, the findings of this study suggests that with additional sessions to account for learning to perform trimanual actions, subject can prove similarly capable to a dyad. Throughout the practice phase learning was clearly observed in all metrics.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Compared to the results of [15], which considered the same coupled motion task, the findings of this study suggests that with additional sessions to account for learning to perform trimanual actions, subject can prove similarly capable to a dyad. Throughout the practice phase learning was clearly observed in all metrics.…”
Section: Discussioncontrasting
confidence: 51%
“…It was found that the addition of the foot controlled hand slowed operation time, however, when the hands acted independently of one another there was otherwise no reduced performance when the hands were uncoupled. The relative performance of trimanipulation was then compared to the use of multiple operators [15]. Three different levels of coupling between the hands were considered, where in all cases the couple outperformed a single trimanual subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such coupling does result in reduced performance and when continuously tracking additionally leads to increased cognitive load [35]. Finally, when comparing subject performance to that of dyads, the dyad has to date outperformed the single user controlling an SE who had higher mental effort in all tested cases [105], [108]. However, the relative difference between results appears to reduce in coupled motion (all all dependent) [108], and might disappear when haptic feedback and some learning is provided [105], although users still reported increased mental effort.…”
Section: Experiments and Applicationsmentioning
confidence: 99%
“…For trimanipulation to be beneficial in everyday life, it should enable users to perform tasks both independently of the natural limbs and in combination with them. The ability of users to perform trimanual coordination has only recently begun to be explored [9], [10]. These studies have shown that users can learn to perform trimanual reaching tasks with virtual foot-controlled supernumerary limbs.…”
Section: Introductionmentioning
confidence: 99%